2014
DOI: 10.1208/s12249-014-0120-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Poly(2-Ethyl-2-Oxazoline) Containing Copolymer Networks of Varied Composition as Sustained Metoprolol Tartrate Delivery Systems

Abstract: Abstract. Segmented copolymer networks (SCN) based on poly(2-ethyl-2-oxazoline) and containing 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, and/or methyl methacrylate segments have been evaluated as potential sustained release systems of the water soluble cardioselective β-blocker metoprolol tartrate. The structure and properties of the drug carriers were investigated by differential scanning calorimetry, attenuated total reflectance Fourier transform infrared spectroscopy, scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…CIP alone demonstrated a sharp characteristic peak at 271.7°C owing to the melting of crystalline nature. Blank PEtOx NPs demonstrated a broad characteristic peak at 65.1°C with a maximum peak point at 82.9°C due to the binding water loss of the blank PEtOx NPs [ 37 ]. The broad endotherms from CIP-loaded PEtOx NPs were comparable with the endothermic peak of blank PEtOx NPs and were similar with the binding water loss of the blank PEtOx NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIP alone demonstrated a sharp characteristic peak at 271.7°C owing to the melting of crystalline nature. Blank PEtOx NPs demonstrated a broad characteristic peak at 65.1°C with a maximum peak point at 82.9°C due to the binding water loss of the blank PEtOx NPs [ 37 ]. The broad endotherms from CIP-loaded PEtOx NPs were comparable with the endothermic peak of blank PEtOx NPs and were similar with the binding water loss of the blank PEtOx NPs.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that CIP has been incorporated with the PEtOx NPs and a minor shift of endothermic peaks indicates the interaction between the polymer and CIP. However, the range of melting points is still very close to the CIP alone (271.7°C) thus no changes of the crystal integrity were found within the prepared formulations [ 37 ]. The same characteristics of the shifted melting peak for CIP were also reported by Bag et al [ 38 ] when CIP was studied to determine its crystalline characteristics in a drug-drug salt formation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, by using water the introduction of organic solvents can be completely avoided. Furthermore, swelling capabilities of poly(2-oxazoline)s have been shown in different studies with copolymer networks 29 and hydrogels. 30 Although not tested in this study, we therefore suggest that swelling behavior of the deposited PnPrOx-layer above the LCST may lead to an increase in thickness.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 99%
“…Hydrogels are advantageous delivery systems for hydrophilic drugs because dissolved drugs could be included in the swollen cross-linked polymer matrix [ 29 , 30 , 31 ]. A variety of network structures could be used for the development of hydrogels suitable for dermal drug delivery applications, including copolymer architectures [ 38 , 39 , 40 ] and interpenetrating (IPN) and semi-interpenetrating networks [ 41 , 42 , 43 ]. A high swelling capacity in water and in body liquids of the networks, which reduces the irritancy of the carrier, is of prime importance, along with the general requirements for biocompatibility and non-toxicity.…”
Section: Introductionmentioning
confidence: 99%